2021
DOI: 10.32800/abc.2021.44.0219
|View full text |Cite
|
Sign up to set email alerts
|

Natural hybridization between immigrant narrow–barred Spanish mackerel Scomberomorus commerson (Lacepède, 1800) and endemic West African Spanish mackerel Scomberomorus tritor (Cuvier, 1832) in the Egyptian Mediterranean coast

Abstract: Immigrant narrow–barred Spanish mackerel, West African Spanish mackerel and specimens with an external appearance somewhere between these putative parents were collected from Abu Qir Bay, East Alexandria, Egypt. The hybrid index results and univariate and multivariate analysis indicated a natural hybridization between these two species. The discriminant function analysis successfully classified individual fish in the data to one of the three fish groups. Squared Mahalanobis distances extracted from the groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…The carnivorous T. lepturus feeds on cephalopods, bony fishes and euphausiids as sub‐adults and adults (Martial et al, 2020; Martins et al, 2005). Bakhoum (2007) revealed that Trichiurus from the Egyptian coast, especially at AbuQir, fed on crustaceans when they were smaller than 30 cm in size, while fish larger than 59 cm tended to eat fish. The oropharyngeal cavity in predatory fish plays several roles including seizing and maintaining grip on prey (including other fish), food selection and the rejection of unwanted excretory particles swallowed by the fish.…”
Section: Introductionmentioning
confidence: 99%
“…The carnivorous T. lepturus feeds on cephalopods, bony fishes and euphausiids as sub‐adults and adults (Martial et al, 2020; Martins et al, 2005). Bakhoum (2007) revealed that Trichiurus from the Egyptian coast, especially at AbuQir, fed on crustaceans when they were smaller than 30 cm in size, while fish larger than 59 cm tended to eat fish. The oropharyngeal cavity in predatory fish plays several roles including seizing and maintaining grip on prey (including other fish), food selection and the rejection of unwanted excretory particles swallowed by the fish.…”
Section: Introductionmentioning
confidence: 99%